Cordia macleodii (Griff.) Hook. f. & Thomson (Boraginaceae) – A comprehensive review (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
Cordia macleodii (Griff.) Hook.f. & Thomson belongs to the family Boraginaceae of flowering plants and is locally known as Dahiman or Dahipalash. It is a highly medicinal and critically endangered plant distributed mainly in dry deciduous forests of India and used by tribal communities of different states of India for making various agricultural and household implements and treating various ailments and diseases. The presence of valuable phytochemicals such as glycosides, flavonoids, saponins, phenols, terpenoids, and fixed oils made this plant more promising for developing modern herbal drugs. These bioactive compounds have been isolated from tree bark, stem andleaves. The plant possesses various pharmacological activities such as antimicrobial, hepato-protective, antioxidant, antivenom, wound-healing, antidepressant, and antihypertensive, with great significance in pharmaceutical industries for developing new herbal drugs. The present review gives an account of taxonomy, ethnobotany, pharmacognosy, phytochemical constituents, pharmacological activities, and conservation status.